The Survival of Acehnese Traditional Markets in the Modernization Era - Nazaruddin, M.; Kamil, Ade Ikhsan; Nasution, Abdullah Akhyar; Aulia, Faizul (SCAD Independent, 2023)
This article examined the sustainability aspects of traditional markets from a socio-anthropological perspective. The author aimed to demonstrate that fundamental changes occur due to the convergence of two economic systems in contemporary society. In the research process, the author employed qualitative research methods using an ethnographic approach. The research took place in Bireuen Regency, Aceh Province, which is located in the western region of the Republic of Indonesia. The study subjects included traders, market visitors, and the surrounding community. Data collection techniques involved interviews, direct observations, and literature reviews. The collected data were analyzed ethnographically by categorizing and connecting all the data to obtain subtopics and their meanings. The research findings revealed the existence of subcultures and societal customs that have been organized and passed down through generations. Traditional markets now coexist with the influences of modernization.